ISTRI YANG BEKERJA DALAM PERSPEKTIF ‎AL-QURAN (Studi Studi Penafsiran M. Quraish ‎Shihab Terhadap Kata Qawwam Dalam Qs. An-‎Nisa/4:34 Dan Penafsiranqs. Al-Ahzab/33:33)‎ - Rahma, Nur Fadhillah (UIN Sumatera Utara Medan, 2020)
Economic difficulties often force wives to work outside the home, even though they may not wish to. This study aims to explore the Quran’s perspective on the status of working wives, based on M. Quraish Shihab's views in QS. An-Nisa / 4:34 and QS. Al-Ahzab / 33:33, which allow wives to work with their husband's consent. Using a thematic exegesis (tafsir Maudhu’i) approach and content analysis, the research finds that M. Quraish Shihab permits wives to work under the conditions of obtaining the husband’s permission, maintaining dignity, preserving their faith, and avoiding negative impacts on themselves and their environment. This perspective offers solutions to the issue of wives working while supporting the family’s economy in line with Islamic teachings.